Bone marrow mesenchymal stem cells preconditioned with nitric-oxide-releasing chitosan/PVA hydrogel accelerate diabetic wound healing in rabbits. (1st March 2021) - Ahmed, Rashid; Afreen, Afshan; Tariq, Muhammad; Zahid, Alap Ali; Masoud, Muhammad Shareef; Ahmed, Maqsood; Ali, Imran; Akram, Zeeshan; Hasan, Anwarul
Abstract: Impaired diabetic wounds are one of the major pathophysiological complications caused by persistent microbial infections, prolonged inflammation, and insufficient angiogenic responses. Here, we report the development of nitric-oxide (NO) -releasing S-nitroso-N-acetyl-penicillamine (SNAP) -loaded chitosan/polyvinyl–alcohol hydrogel and its efficacy in enhancing the wound-healing potential of bone marrow mesenchymal stem cells in diabetic wounds. NO-releasing hydrogels significantly increased the cell viability and cell proliferation of hydrogen-peroxide (H2 O2 ) -pretreated bone marrow stem cells (BMSCs), demonstrating their cytoprotective activity, which was further confirmed by gene expression of many times as much B-cell lymphoma 2 (Bcl-2), stromal cell-derived factor-1alpha (SDF-1α), proliferating cell nuclear antigen (PCNA) and vascular endothelial growth factor (VEGF). Furthermore, the SNAP-loaded hydrogel showed continuous cell-proliferating activity for six days, due to the slow release of NO from the hydrogel. Wound-healing studies of rabbits with induced diabetes showed that the application of SNAP-preconditioned BMSCs and NO-releasing hydrogels significantly sped up the healing process, compared to the control group. The wound-healing potential of BMSCs plus NO-releasing hydrogel was further validated by improved collagen deposition and epithelial layer formation, as confirmed by histopathological examination, as well as upregulation of VEGF and SDF-1α biomarkers, as evidenced by gene-expression analysis. These results demonstrated that the application of BMSCs with NO-releasing hydrogel can promote faster regeneration of damaged tissues. Therefore, BMSCs plus NO-releasing hydrogels can be very useful for the treatment of diabetic wounds.